THE IMPORTANCE AND NEED OF THE SOCIAL WORKER IN THE PREVENTION OF CHILD VIOLENCE - Maftuna Karimova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article focuses on the importance of social, political and legal protection of minors and the improvement of the social consciousness formation system aimed at its vital development. issues of formation of national values, ideological immunity in cultivation are highlighted. Also, as a result of the analysis of the consequences of the victims of violence and empirical research, proposals for the introduction of a system of preventive measures in working with children subjected to violence are scientifically covered.